A Nonagonal Framework of Regulation in Talent Development (NFRTD). (3rd July 2019) - Ziegler, Albert; Stoeger, Heidrun
ABSTRACT: Regulatory processes are pervasive on many levels in talent development, yet neither a systematic analysis of their role in talent development let alone a comprehensive model have been presented to date. The aim of this article is to demonstrate the diversity and complexity of regulatory processes in talent development and to provide a conceptual framework. The proposed nonagonal framework of regulation in talent development (NFRTD) distinguishes nine dimensions for the analysis of regulation in talent development: regulatory network (neutral, co-operative, competitive, hybrid, and panarchic), regulatory function (homeostasis and homeorhesis), control type (external, internal-automatic, and internal-controlled), regulatory type (open-loop control and closed-loop control), regulatory form (iterative and recursive), regulatory activities (preventive, detective, and corrective), regulated structures (exogenous and endogenous learning resources), regulatory side-effects (neutral, synergetic, destructive, catalytic, exploitative, and allostatic), and regulatory externalities (neutral, iatrogenic, and autocatalytic). The last section discusses the status of the nonagonal framework and hints at some fields of application.